2007
DOI: 10.1128/jcm.00156-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aerococcus viridans Isolates from Swine Clinical Specimens

Abstract: We present here the biochemical and genetic characterization and antimicrobial susceptibility of 58 isolates of Aerococcus viridans isolated in pure culture from different clinical specimens of normally sterile body sites of pigs. A. viridans isolates were commonly susceptible to ␤-lactam antimicrobials and exhibited a great genetic heterogeneity as determined by pulsed-field gel electrophoresis typing. The results indicate that A. viridans might be included in the list of possible etiological agents causing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 23 publications
6
37
0
Order By: Relevance
“…The identity of ERIC1R generated PCR profiles clearly suggests that strains LK 13 and Str 13 from Liptovska Kokava or Budča farms are clonaly related. This observation is in contrast to data obtained by Martin et al (2007) who indicated an exposure of swine to multiple A. viridans strains, what is in accordance with the wide distribution of A. viridans (Woodward et al 1998), and also suggests an opportunistic pathogenic character of this bacterium. Similarly, Kagkli et al (2007) reported the presence of putative new A. viridans species in Gram-positive cocci from raw milk in a farm dairy environment.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The identity of ERIC1R generated PCR profiles clearly suggests that strains LK 13 and Str 13 from Liptovska Kokava or Budča farms are clonaly related. This observation is in contrast to data obtained by Martin et al (2007) who indicated an exposure of swine to multiple A. viridans strains, what is in accordance with the wide distribution of A. viridans (Woodward et al 1998), and also suggests an opportunistic pathogenic character of this bacterium. Similarly, Kagkli et al (2007) reported the presence of putative new A. viridans species in Gram-positive cocci from raw milk in a farm dairy environment.…”
Section: Discussionsupporting
confidence: 45%
“…Owens et al (1991) reported prevalent resistance to streptomycin (60%) followed by tetracycline (23%), erythromycin (17%), penicillin (16%) and ampicillin (13%). Completely different profiles were reported for A. viridans isolates from swine clinical specimens (Martin et al 2007). These A. viridans isolates were commonly susceptible to beta-lactam antimicrobials, but resistant to streptomycin (90%), tetracycline (95%) and erythromycin (59%).…”
Section: Discussionmentioning
confidence: 99%
“…Sequences closely related to the common opportunistic pathogen Aerococcus viridans, which is associated with arthritis in swine (Martin et al 2007), were found in all environments except the Swine A nursery. A. viridans has been cultured from environmental aerosol samples in previous studies (Williams et al 1953;Kerbaugh and Evans 1968).…”
Section: Discussionmentioning
confidence: 99%
“…MICs values were similar to those found in our study with V. fluvialis CD264. Martín et al (2007) tested 58 A. viridans isolates for their susceptibility to 12 antimicrobials using the disk diffusion method. They found that A. viridans isolates were slightly resistant to streptomycin, erythromycin, clindamycin and tetracycline.…”
Section: Safety Assessmentmentioning
confidence: 99%
“…Kerbaugh and Evans (1968) also underlined such phenotype for A. viridans isolated from hospital environment. Moreover, A. viridans is a crustacean pathogen, causing the lobster's gaffkemia disease, and has been associated with different human infections such as endocarditis, urinary tract infections, arthritis, or meningitis (Kerbaugh and Evans, 1968;Martín et al, 2007).…”
Section: Safety Assessmentmentioning
confidence: 99%